Odpowiedzi

2010-01-16T19:05:39+01:00
A)5:x=4:3;x=0

b)3:5=x;10 /*10
6=x

c)x/7=4/5 /*35
5x=28
x=5 3/5

d)5x-3/9=3x-7/5 /*45
25x-15=27x-63
-2x+48=0
x=24

e) 3(x-1)/3=-x-7/5 /*15
15(5x-5)=3x-21
75x-75=3x-21
72x-54=0
x=1/3

f)x-3/8=x+3/12 /*24
3x-9=2x+6
x=15

g)4+8x/2=3(x+13)/7 /*14
28+56x=6(2x+26)
28+56x=12x+156
-128+44x=0
x=2,9

h)5(x-2)/3=5x-20/4 /*12
20(4x-8)=15x-60
80x-160=15x-60
65x-100=0
x=1,53

i)4-x/3=x+6/2 /*6
8-2x=3x+18
-10-5x=0
x=-2

j)3(x-2)/5=4(x+3)/3 /*15
9(3x-6)=20(5x+15)
27x-54=100x+300
-73x+246=0
x=3,36
1 1 1